Green Construction and Local Wisdom Integration for Sustainability: A Systematic Literature Review - Sri Kristinayanti, W.; Zaika, Yulvi; Padma Devia, Y.; Solimun, .; Agung Wibowo, M. (Salehan Institute of Higher Education, 2024)
The construction industry's environmental impact necessitates a sustainable shift to mitigate resource depletion, emissions, and biodiversity loss. Integrating local wisdom offers innovative, adaptive solutions grounded in deep environmental understanding, potentially transforming construction practices toward sustainability. This study aims to identify aspects, challenges, impacts, and strategies in green construction practices integrated with local wisdom. The PRISMA framework methodology was used to conduct a comprehensive systematic review with qualitative analysis using NVivo software. Nine aspects of green construction integrated with local wisdom were identified, with cultural heritage preservation the dominant aspect. Eleven challenges were uncovered, with balancing tradition and innovation as the main challenges. Seven impacts on the economy, society, and environment were identified, with construction cost efficiency, improvement of community quality of life, and promotion of a circular economy and sustainable waste management as the dominant impacts. Thirteen strategies were identified, with active engagement of local communities in the construction process as the main strategy. The novelty of this research is a comprehensive review of the integration of green construction with local wisdom, which can be used as a guide in sustainable construction practices responsive to local environmental and social conditions and promote economically, socially, and environmentally sustainable development. Doi: 10.28991/CEJ-2024-010-11-020 Full Text: PDF